KRAS mutations in metastatic colorectal cancer: from a de facto ban on anti-EGFR treatment in the past to a potential biomarker for precision medicine. (3rd October 2021) - Coupez, Dahna; Hulo, Pauline; Touchefeu, Yann; Denis, Marc G; Bennouna, Jaafar
ABSTRACT: Introduction: The high frequency of RAS mutations, particularly KRAS mutations, in colorectal cancer (CRC) and the ineffectiveness of anti-EGFR antibodies in treating this disease has created a significant unmet medical need, especially for treating patients in the metastatic phase of this disease. There are many different types of RAS mutations, the most frequent being G12V (c.35 G > T (p.G12V)), G12D (c.35 G > A (p.G12D)), and G13D (c.38 G > A (p.G13D)). Here, we provide an overview of RAS mutations in CRC and their therapeutic implications. Areas covered: The therapeutic strategies against metastatic CRC with RAS mutations are elaborated according to patient and disease characteristics and integrated into a multiline strategy. The complexity of the molecular structure of RAS and its relationship with the MAPK/ERK pathway partly explain the initial therapeutic failure with MEK or farnesyltransferase inhibitors. Conversely, the development of direct KRAS inhibitors or drugs targeting RAS regulators (e.g. SOS1 and SHP2) has opened new therapeutic fields, requiring the distinction of each KRAS mutation type. Expert Opinion: In the future, KRAS inhibitors, including SOS1 and SHP2 inhibitors, might be used in combination with other signal transduction inhibitors, such as MEK inhibitors or anti-EGFR antibodies, which block alternative pathways of activation.